Cyber crime investigator's field guide - Middleton, Bruce (Auerbach Publications, 2005)
The movement toward miniaturized and mobile computing has created more opportunity for cyber thieves. To respond effectively, IT security professionals need a resource that combines the understanding of investigative techniques with the technical knowledge of cyberspace. Cyber Crime Investigator's Field Guide, Second Edition provides an investigative framework, demonstrates the knowledge of how cyberspace really works, and explains the tools needed to pursue cyber criminals. This volume provides the details of investigating computer crime from soup to nuts. It covers the entire investigative p.